Food Coping Strategies dan Aplikasi Pemantau Status Gizi Sebagai Upaya Preventif Stunting - Berliana Devianti Putri; Nur Septia Handayani; Fitri Retrialisca; Riris Medawati; Imroatul Hafidzah; Rahmi Romadhona Salsabila Putri (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Stunting is a chronic nutritional deficiency prone to occur in children due to a lack of nutritional intake for a long time starting before the mother is pregnant and until the child is two years old. It is necessary to provide information and education about prevention, early detection and efforts to fulfill nutritional needs.This community service activity aims to increase knowledge of stunting early detection, how to prevent stunting, and improve food coping strategies skills in the household by utilizing food ingredients that are easily found in the surrounding environment. The method used is the preparation of a book with the title